2017
DOI: 10.1007/s12253-017-0242-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Molecular Study of Triple-Negative Breast Cancer in Algerian Patients

Abstract: Triple-negative breast cancer (TNBC) is associated with aggressive tumor behavior, poor prognosis and BRCA1 mutations. There are limited data regarding TNBC among Algerian women. In this study, we sought to determine clinical and tumor characteristics associated with TNBC. We also screened for the prevalence of BRCA1 mutations in unselected cohort of TNBC patients. Clinical and tumor characteristics data of 877 breast cancer patients diagnosed between 2011 and 2015, were collected from cancer registry of publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…Thus, the clinical data associated to exon 11 mutations tend to be homogeneous. As for the pathological data, most of BRCA1 mutations located in exon 11 have been correlated with high grade TNBC, large tumor size (>2cm) and poor prognosis, as our patient, leading to a genotype phenotype correlation [22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, the clinical data associated to exon 11 mutations tend to be homogeneous. As for the pathological data, most of BRCA1 mutations located in exon 11 have been correlated with high grade TNBC, large tumor size (>2cm) and poor prognosis, as our patient, leading to a genotype phenotype correlation [22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 59%
“…As well, in this Tunisian family, detection of this mutation in relative's diagnostic with BC or ovarian cancer would have been an additional argument in favour of the segregation of this mutation with the disease. Several studies reported different disease phenotypes among patients carrying mutations in exon 11 of BRCA1 compared to other BRCA1 germline mutations [22][23][24][25][26][27][28]. Rebbeck et al (2015) reported a total of 19 581 females carrying BRCA1 mutation of which 1132 had a nonsense mutation in exon 11, 796 BC and 336 ovarian cancer, with a mean age at cancer diagnosis 40, 4 and 50, 2-year-old respectively, likewise our IC who had an early onset age of cancer (BC: 38 years old, ovarian cancer: 50-years-old) [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been also found in the United Kingdom [1]. More recently, it has been reported in Algeria in three young patients aged 33, 34 and 38 years respectively, all with triple negative cancer and a family history of breast and/or prostate cancer [47].…”
Section: Discussionmentioning
confidence: 79%
“…It was also identified in two Tunisian and Algerian families with a common haplotype to all carriers of this mutation [20], suggesting the presence of the first non-Jewish founder effect in North Africa. It was later identified in four Algerian patients [21,47], three Moroccan women [16,17] and five Tunisian women [22], all with a family history of breast or ovarian cancer and aged between 34 and 44 years.…”
Section: Discussionmentioning
confidence: 99%
“…2 This finding is in agreement with previous studies in patients with TNBC from Tunisia. 15 A recent study conducted in Morocco highlighted the high frequency of BC in young women as compared with Western countries. 23 In this study, both TNBC and non-TNBC cases prevail in younger women, with no statistical difference between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%